Hijrah as Socio-Religious Transformation among Non-Hijabi Muslim Women in Singaraja, Bali - Muhammad Idris; Alif Alfi Syahrin; Irwan Nur; Ana Safitri; Nia Septinawati; Adinda Cinderalaila Fathonatan Ryantho; Mahir Pradana (Balai Penelitian dan Pengembangan Agama Semarang, 2026)
The phenomenon of hijrah is widely examined through visible symbolic changes, such as adopting the hijab. However, a significant research gap exists regarding how non-hijabi Muslim women interpret this transformation, particularly within minority contexts where their academic perspective remains underexplored in previous literature. This case study investigates the socio-religious transformation and identity construction of non-hijabi Muslim women in Singaraja, Bali. Singaraja was selected as a unique multicultural space where a Muslim minority community interacts closely with dominant Balinese cultural dynamics. Using a qualitative approach, data were gathered through in-depth interviews with fifteen participants, a sample size justified by data saturation, where no new themes emerged during iterative collection. The data were systematically analyzed using thematic analysis. The findings concretely reveal that participants understand hijrah not as an appearance-based milestone, but as a continuous, internal process of spiritual and moral self-improvement. This transformation is experienced through explicit personal actions, such as internalizing sincerity, refining character, improving worship consistency, and consciously practicing interreligious tolerance amidst local cultural values. Furthermore, digital media and social environments exert structural pressures by projecting idealized visual standards of piety. In response, these women exercise distinct spiritual agency by separating authentic religious conviction from visual conformity. This study contributes empirically grounded evidence demonstrating how minority Muslim women fluidly negotiate identity and sustain religiosity without fully submitting to dominant symbolic expectations.